Textbook of operative dentistry - Sikri, Vimal K. (New Delhi : Cbs Publishers, 2014)
This textbook has been in the market for over 12 years, receivmq much acclaim and appreciation from the students, teachers and clinicians. Keeping pace with the evolving technologies and acknowledging the dynamicity of the subject, the third edition highlights the following key-features. Five new chapters included viz. 'Dentin repersensitivity', 'Geriatric Restorations', 'Laser in Operative Dentistry ',' Esthetic Dentistry and Management of Deep Carious Lesions. Recent developments added in every chapter. A few chapters like 'Direct Filling Gold', though not of much clinical importance, retained as per the curriculum of the universities. Many fresh illustrative color diagrams and tables added. Text updated, reorganized and reset completely.Precise details of clinical procedures presented with relevant photographs and Emphasis maintained on the lucidity of language and expression. This edition covers syllabi of all the universities/Dental Council of India. The Textbook aims to serve the much expected purpose of inspiring the students, teachers, clinicians.
Includes index.
dental bookfair2015
Keywords: Dentistry, Operative